Viewing Quantum Charge from the Classical Vantage Point. Issue 5 (10th December 2022) - Gilton, Marian J. R.
Abstract: This article demonstrates the benefit of studying a classical version of chromodynamics in order to better understand color charge in quantum chromodynamics. Standard presentations of the conservation and confinement of color charge serve to obscure the Lie-algebra-valued character of the conserved Noether charge. This article shows how we can remove these obscuring factors by studying color charge from the vantage point of classical chromodynamics. This key example of color charge illustrates the larger methodological benefit of this classical vantage point: interpreting classical gauge theories helps to delineate the uniquely quantum features of quantum field theories.